Realization of sports talent in youngsters in context of sociological analysis - Ponomarev, A. V.; Popova, N. V.; Tropina, N. K.; Popov, A. N. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to analyze and summarize the opinions of young athletes about realization of sports talent. Methods and structure of the study. We analyzed the world's and domestic experience of work with gifted in sports youngsters, identified the opportunities for realizing their sports talent, as well as determined the positive and negative aspects of the system of support to the gifted and talented in sports youth that exists in the Sverdlovsk region. We carried out an expert opinion poll, with the leading student athletes of Ural Federal University being subject to the poll, as well as individual interviews with gifted in sports schoolchildren and students. We studied the opinions of young professional athletes about their sports achievements and assessment of the current situation in sports, compiled proposals for supporting gifted athletes.